The Effect of Concentrated Liquids Before Physical Exertion on Some Physiological Variables of 10,000 Meters for Young Runners - Ahmed Abdulrazzaq Fadhil; Emad Amanah Kaittan; Mohammed Amanah Kaittan (Indian Journal of Forensic Medicine & Toxicology, 2021)
The objective of the research is to identify the effect of concentrated fluids before physical exertion onsome of the physiological variables of the 10,000-meter runners of youth for the individuals of the researchsample, to identify the speed of the hostile response 10,000 meters to the concentrated fluids before thephysical exertion of the individuals of the research sample. The research sample was determined by thedeliberate selection of young runners in athletics age (18-19 years) according to the classification of theInternational Athletics Federation, as the research sample included (21) runners representing Baghdad clubsand the National Center for Sports Giftedness, they were distributed randomly (by drawing lots) into threegroups, each group consisting of (7) runners, energy and speed of recovery, thus increasing the maximumoxygen consumption and total energy drainage, sugar and sodium chloride have a great effect on energyproduction and thus increase the maximum oxygen consumption and total energy drainage, as for water, itdid not have a significant effect in increasing the maximum oxygen consumption and total energy drainage.The researcher recommended using concentrated liquids with water an hour and a half before running longdistances. From fatigue and increases the speed of recovery, drinking concentrated fluids before, during, andafter long-distance runs reduces the incidence of fatigue, thus delaying the onset of lactic acid and increasesenergy production.